2013
DOI: 10.2175/193864713813673316
|View full text |Cite
|
Sign up to set email alerts
|

Demand Management Strategies Resulting In “Zero and Low Cost” Energy Saving Opportunities for Water and Wastewater Treatment Facilities

Abstract: Reducing energy costs is rapidly becoming a major priority for water and wastewater utilities. As a result, many water and wastewater utilities are performing energy management audits and evaluations to identify energy saving opportunities that will provide energy benefits at the lowest possible capital cost. Many water and wastewater facilities can realize "zero or low cost" energy saving opportunities through managing their energy demand in coordination with the energy billing rates. This is especially true … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The diffusion of smart grids, favoured by the diffusion of solar and wind electricity sources, have triggered several studies which investigated the possibility of moving WRRF peak consumption in time, thereby decreasing their carbon footprint. Lisk and Long (2013) and Kirchem et al (2018) concluded that both wastewater transport and treatment can provide substantial flexibility in electricity consumption. Further investigations of the WRRF electricity consumption have identified aeration as the most demanding step, accounting for about 50% of total consumption (Longo et al 2016).…”
Section: )mentioning
confidence: 99%
“…The diffusion of smart grids, favoured by the diffusion of solar and wind electricity sources, have triggered several studies which investigated the possibility of moving WRRF peak consumption in time, thereby decreasing their carbon footprint. Lisk and Long (2013) and Kirchem et al (2018) concluded that both wastewater transport and treatment can provide substantial flexibility in electricity consumption. Further investigations of the WRRF electricity consumption have identified aeration as the most demanding step, accounting for about 50% of total consumption (Longo et al 2016).…”
Section: )mentioning
confidence: 99%